Anisotropy and directional shrinkage of geosynthetic clay liners. Issue 3 (June 2010) - Bostwick, L.; Rowe, R.K.; Take, W.A.; Brachman, R.W.I.
Abstract : ABSTRACT: Results are reported from laboratory experiments to examine the potential shrinkage of two different geosynthetic clay liners (GCLs) when subject to repeated wetting and drying cycles. One GCL had a scrim-reinforced nonwoven carrier geotextile (denoted as GCL2) and the other had a nonwoven carrier geotextile (GCL4). Tests were conducted with both restrained and unrestrained GCL specimens of the same size as well as restrained specimens with different specimen sizes and length-to-width aspect ratios. For unrestrained specimens, there was no apparent difference between shrinkage in the transverse and longitudinal directions for GCL2, whereas GCL4 tended to shrink more in the longitudinal direction. There was only a small difference between restrained and unrestrained tests, with the restrained specimens giving a maximum strain about 1.1 times higher than the unrestrained for GCL4. There was no clear effect of the specimen size on the measured shrinkage. For restrained specimens, shrinkage increased with increasing aspect ratio up to an aspect ratio of approximately 5. The dry mass per unit area of the product was found not to affect shrinkage when the mass per unit area was evenly distributed. However, specimens with an uneven bentonite distribution (typically those with a low mass per unit area) can have areas of little to no bentonite content, and these specimens experienced much higher shrinkage than other specimens. A high degree of variability between specimens for apparently similar test conditions was observed. Even more noteworthy is the fact that the maximum shrinkage observed in these tests (14.4%) was well below the maximum of 23% observed by previous investigators using the same methodology and nominally the same product. This shows the difference that can occur between different rolls of nominally the same product.